Employee Performance Improvement Strategy TB Harris Jaya Bandung - Suharna Suharna; Rinda Anggraeni (SINTESA, 2022)
The focus of this research is not optimal performance of TB employees. Harris Jaya Bandung. Based on this, this study aims to determine the implementation of employee performance improvement strategies and efforts to implement TB employee performance improvement strategies. Harris Jaya Bandung. This study uses a qualitative research method approach with the research variable is an employee performance improvement strategy. The sampling technique was carried out by purposive sampling technique. Research informants as many as 6 people consisting of owners and employees. The research data were analyzed using the Miles and Huberman model with steps including data collection, data reduction, data presentation, and drawing conclusions. The results showed that the implementation of the TB employee performance improvement strategy. Harris Jaya Bandung is good, this can be seen from the dimensions of 1) quantity, 2) quality, 3) timeliness, 4) cost effectiveness, 5) need for supervision ), and 6) the interpersonal impact is in line with the expectations of TB employees. Harris Jaya Bandung. Furthermore, efforts to overcome performance barriers need to be made as material for obligations, duties and responsibilities that require employee services because the success of an organization in carrying out its duties can be seen again the performance of its employees. Performance strategies that can be achieved by employees at TB. Harris Jaya Bandung, in accordance with their respective authorities and responsibilities.